International shipping cartels : a study of industrial self-regulation by shipping conferences - Marx, Daniel (New York : Greenwood Press, 1969)
Shipping conferences are among the earliest cartels in international trade. The purpose of this volume has been to describe and analyze as objectively as possible the functioning of these organizations for self-regulation.
Includes bibliographical footnotes and index.
ne 21/01/2019
Loans
Keywords: Shipping conferences; Shipping conferences--Law and legislation